Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan - Indah Respati Kusumasari (Majalah Ilmiah DIAN ILMU, 2022)
This study aims to determine the effect of work motivation and work discipline on employee performance partially and simultaneously. The type of research used is descriptive research with a quantitative approach. The sample used was 35 respondents with saturated sampling technique. The data analysis technique used in this research is multiple linear regression analysis, using the F test and t test. The results of multiple linear regression showed that work motivation had a significant effect on employee performance with a t-value of 5.924 > t-table 1.990. The work discipline variable shows a t-value of 4.650 > t-table 1.990, this means that it has a significant effect on employee performance. The result of F-value is 50.604 > F-table 3.112, that there is a significant influence between the variables of work motivation and work discipline that simultaneously affects employee performance.